(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A new single phase transformer less Photovoltaic (PV) inverter for grid tied PV systems. The topology is derived from the concept of a charge pump circuit in order to eliminate the leakage current.It is composed of four power switches, two diodes, two capacitors and an LCL output filter. The neutral of the grid is directly connected to the negative polarity of the PV panel that creates a constant Common Mode (CM) voltage and zero leakage current. The Charge pump circuit generates the negative output voltage of the proposed inverter during the negative cycle. Characterized by higher efficiency and lower cost. In this context, new topologies, modulation, and control schemes were presented to solve problems of a common-mode voltage and leakage current. This work proposes a transformer less five-level inverter with zero leakage current and ability to reduce the harmonic output content for a grid-tied single-phase PV system. The neutral of the grid links to a common on which the negative and the positive terminals of the DC-link are connected via parasitic capacitors that can eliminate the leakage current. The proposed topology, with its inherent circuit structure, leads to boost the overall efficiency. Simulation and experimental results show almost zero leakage current and a high-quality output when maintaining balanced capacitor voltages on the DC-link input. The experimental results show 1.07% THD and 96.3 % maximum efficiency when injecting a power of 1.1 kW that verify the performance of the proposed inverter with PV source